Pragmatism and Positivism - Nekrašas, Evaldas (Problemos, 2001)
Like positivism, pragmatism is a kind of scientifically oriented philosophy. They have much in common. Both represent the conviction that the development of science is a decisive factor in the progress of humanity. Both share the opinion that the source of real knowledge is experience and both treat the British empiricists as their forerunners. Both pragmatism and positivism (especially 20th century positivism) are anti-dogmatic and claim that philosophy is a method rather than theory. The theories they, nevertheless formulate, resemble each other. Specifically, their theories of meaning exhibit quite a great degree of affinity. Pragmatism attaches great importance to the practical efficacy of our concepts and theories but Auguste Comte also claimed that the positive mind is interested only in what is useful and practical.
Keywords: positivism; pragmatism; logical positivism; metaphysics; experience